KUALITAS PELAYANAN RESEPSIONIS DI GRAND ELITE HOTEL PEKANBARU - Churcill, Vivyan Augustine E; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research aims to determine the quality of reception services at Grand Elite Hotel Pekanbaru. This research uses quantitative methods to examine the problems raised. The samples in this study were 50 people using accidental sampling technique. While the data collection techniques in this research used the method of distributing questionnaires, observation, and interviews. The measurement technique used in this research questionnaire is a Likert scale, then the data will be processed using quantitative methods whose data is numerically oriented to results in the form of definite and clear conclusions. Based on the results of the research that has been done, there are five dimensions that will be examined in the quality of service at the reception of Grand Elite Hotel Pekanbaru including the first direct evidence such as complete facilities at the Grand Elit Hotel, free facilities provided by the Grand Elite Hotel in the form of breakfast, internet connection and SPA. The second aspect is empathy such as employee friendliness, providing clear information to guests, and employee care for guests. Next, reliability is like the employee who is on time to pick up and deliver guests, employees who are able to fulfill the wishes of guests, and the alertness of employees. Then responsiveness such as employees who are active in serving guests, employees provide responsive services, and employees understand the wishes of guests. And the last one is guarantees like, honesty of employees who create trust for guests, politeness of employees in serving guests, and the ability of employees to provide services. For the whole of the calculation results prove that the quality of reception services at Grand Elite Hotel Pekanbaru is good. Keywords: Receptionist, Service Quality, Reception, Grand Elite Hotel